Duas escritas : o discurso científico e a narrativa literária em Casa-Grande & Senzala - Alves, Tatiana Batista (2007)
The thesis detects that Casa-grande & Senzala, by Gilberto Freyre, is built through two fundamental bases the scientific discourse and the literary narrative , which communicate harmonically and establish a singular semantic field within Social Sciences in the beginning of the twentieth century. This could be realized as we verified in the freyrean text sociologic essay the production of some images that are not part of the scientific category. This way, we evaluate these parts, examining in which way the semantic construction is built, and we are able to identify the presence of several literary marks. Some of the main ideas of the text, among which is the myth of racial democracy surpass the concept field, once they are produced through a literary expression, that is, a verbal construction capable of producing meanings which transcend language itself. After the inventory of the main images built in the text, we can conclude that Casa-grande & Senzala provided one of the richest, newest, most polemic and contradictory interpretations of Brazil. In order to affirm and prove that the Brazilian society and culture are of a hybrid nature, the author also produces a hybrid text which communicates with several ways or representation, establishing, thus, a perfect communion between the investigation object and the text which represents it.